(untitled) (Discourse of Law and Administration, 2025)
The article deals with the basic issues related to the use of modern information and communication solutions in administrative evidence proceedings. The assessment of the functionality of the electronic document, referred to in Article 3(2) in conjunction with Article 3(1) of the Act on Informatisation of the Activities of Entities Performing Public Tasks in administrative evidence proceedings, in the context of changes in the Code of Administrative Procedure resulting from the Act on Electronic Delivery of Documents, was treated as particularly important. In connection with the resignation – as a result of the amendment – from using i.e., the following terms: “electronic document”, “form of an electronic document” within the meaning of the Act on Informatisation of the Activities of Entities Performing Public Tasks, the assessment of the legal character of an electronic document in administrative proceedings becomes an even more complex legal issue than it used to be. It is therefore fundamental to define the semantic scope of the term “electronic document” in legal terms in the context of regulations of the Code and to assess its essence and function in the phase of administrative evidence proceedings. In particular, it will be crucial to determine the relationship between the “document recorded in electronic form” within the meaning of Article 14 § 1a of the Code of Administrative Procedure and the “electronic document”, as well as between it and the document in electronic form admitted as evidence and other evidence recorded electronically in the administrative evidence procedure.